tive Epidemiological Study of TB Occurrence In Matraman District Health Center Post Covid-19 Pandemic - Faridi, Ahmad; birwin, Alib; Furqan, Mohammad; Maryusman, Taufik; Setyawan, Arif (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Objective :Tuberculosis (TB) is caused by Mycobacterium tuberculosis bacteria and is transmitted through coughing, sneezing, talking, or spitting. TB cases are more common in men than women and are higher in areas with poor living conditions and low socio-economic status. In 2018, East Java had 56,445 TB cases, with 31,211 cases in men and 25,234 cases in women. Puskesmas Kecamatan Matraman had 630 suspected TB cases in 2020, with 108 confirmed cases and a low TB CDR achievement. Methods: This is a descriptive study aimed at describing the frequency distribution pattern of Tuberculosis (TB) occurrences according to the variables of person, place, and time using a cross-sectional/prevalence study design approach. The study sample consisted of 159 individuals who were Tuberculosis (TB) patients, and the sample was selected using purposive sampling that met the inclusion and exclusion criteria. Results : show the gender and age group of TB patients. The study found that the majority of TB patients at Puskesmas Kecamatan Matraman were male. The proportion of male TB patients ranged from 55.45% to 67.5%, along with other factors such as lifestyle and environment. Most TB patients were in the productive age group of 15-59 years, Conclusion:indicating the need for prevention and control efforts targeted at this group, such as improving knowledge and awareness of TB, promoting healthy lifestyles, and providing accessible and quality health services. Diagnosis of TB patients can be done through microscopic examination or culture.